Effect of Thoracic Gas Volume Changes on Body Composition Assessed by Air Displacement Plethysmography after Rapid Weight Loss and Regain in Elite Collegiate Wrestlers - Kondo, Emi (Sports (Basel), 2019)
We investigated the effect of rapid weight loss (RWL) and weight regain (WR) on thoracic gas volume (V(TG)) and body composition assessment using air displacement plethysmography (ADP) in male wrestlers. Eight male elite collegiate wrestlers completed a RWL regimen (6% of body mass) over a 53-h period, which was followed by a 13-h WR period. ADP was used at three time points (baseline (T1), post-RWL (T2) and post-WR (T3)) according to the manufacturer’s testing recommendations. The total body water and bone mineral content were estimated using the stable isotope dilution method and dual energy X-ray absorptiometry, respectively, at the same time points. Body composition was assessed with two-component (2C) or four-component (4C) models using either the measured V(TG) (mV(TG)) or predicted V(TG) (pV(TG)). Measured V(TG) increased from T1 to T2 (0.36 ± 0.31 L, p < 0.05) and decreased from T2 to T3 (−0.29 ± 0.15 L, p < 0.01). However, the changes in fat mass and fat free mass, which were calculated by both 2C and 4C models, were not significantly different when compared between calculations using mV(TG) and those using pV(TG). Our results indicate that V(TG) significantly changes during RWL and WR, but both measured and predicted V(TG) can be used to assess changes in body composition during RWL and WR.